Biblical commentary on the Psalms ; v. 3 - Delitzsch, Franz Julius, 1813-1890; Bolton, Francis; Wetzstein, J.G. (London, UK Hodder and Stoughton, 1889)
Contents : v. 3 : Psalms 90-150. Includes bibliographical references and indexes.
Keywords: Bible. O.T. Psalms XC-CL -- commentaries